1986
DOI: 10.1002/jhrc.1240091120
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of molecular structures of aza‐arenes by retention indices and fluorescence spectra

Abstract: SummaryTwo methods are described for predicting the molecular structuresof ara-arenes eluted from acapillarycolumn.Thefirst is based on a combination of retention indexes (RI) and a postcolumn reaction. The RI of an aza-arene is calculated by using the incremental contributionsof some atomic groups to RI. Once the molecular weight is determined by the mass spectrum, the possible compounds are picked up, based on comparison of the observed RI with the calculated RI values and information about the intramolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Characterization based on thermodynamics such as the solubility parameter is very important for the theoretical comprehension of chromatography but its application to the experimental evaluation of individual chromatographic systems does not seem to be easy. In GC, the concept of the retention index system introduced by Kovats 5 has succeeded in the prediction of the molecular structure of solutes 6 and especially in the practical characterization of the stationary phases in GC. 7,8 The McReynolds constants 8 are very popular among gas chromatographers; the values are based on the retention indexes of 10 typical standard solutes.…”
mentioning
confidence: 99%
“…Characterization based on thermodynamics such as the solubility parameter is very important for the theoretical comprehension of chromatography but its application to the experimental evaluation of individual chromatographic systems does not seem to be easy. In GC, the concept of the retention index system introduced by Kovats 5 has succeeded in the prediction of the molecular structure of solutes 6 and especially in the practical characterization of the stationary phases in GC. 7,8 The McReynolds constants 8 are very popular among gas chromatographers; the values are based on the retention indexes of 10 typical standard solutes.…”
mentioning
confidence: 99%
“…However, they also showed that a shape factor influenced retention on liquid crystal phases. Morishita et al (23) predicted the structures of azaarenes eluted from silicone and glycol phases based on the contributions of various molecular structure groups to the retention index. Howery and Soroka (24) used factor analysis to identify solute and sorbent properties affecting retention indexes of a set of hydrocarbons on various sorbents.…”
mentioning
confidence: 99%